PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP EFFECTIVE TAX RATE (STUDI EMPIRIS PADA BUMN YANG TERDAFTAR DI BEI 2009-2011) - Rodhian Hanum, Hashemi; Zulaikha, Zulaikha (Diponegoro Journal of Accounting, 2013)
This study aims to examine the influence of Corporate Governance Characteristics consisting of:Independent Commissioner, Audit Committee and the Institutional Shareholders on the EffectiveTax Rate. This study is an empirical research with the purpose of sampling techniques in datacollection. Secondary data obtained from financial statements that have been privatizedgovernment enterprises and listing on the Stock Exchange during the year 2009 to the year 2011.Multiple regression analysis was conducted using SPSS version 16.00 for windows. The test resultsshowed that of the three hypotheses proposed hypothesis none accepted hypothesis. Hypothesis 1(the proportion of independent commissioners positive effect on effective tax rate), hypothesis 2(the size of the audit committee is a positive influence on effective tax rate) and hypothesis 3(institutional investors a positive effect on effective tax rate).